Direct Spectrophotometric Assay for Benzaldehyde Lyase Activity. (14th July 2011) - Natalia, Dessy; Kohlmann, Christina; Ansorge-Schumacher, Marion B.; Greiner, Lasse
Abstract : Benzaldehyde lyase from Pseudomonas fluorescens Biovar I. (BAL, EC 4.1.2.38) is a versatile catalyst for the organic synthesis of chiral α -hydroxy ketones. To allow fast assessment of enzyme activity, a direct spectrophotometric assay is desirable. Here, a new robust and easy-to-handle assay based on UV absorption is presented. The assay developed is based on the ligation of the α -hydroxy ketone (R)-2, 2′-furoin from 2-furaldehyde. A robust assay with direct monitoring of the product is facilitated with a convenient concentration working range minimising experimental associated with low concentrations.